2020
DOI: 10.1002/glia.23888
|View full text |Cite
|
Sign up to set email alerts
|

Astroglial N‐myc downstream‐regulated gene 2 protects the brain from cerebral edema induced by stroke

Abstract: Brain edema is a grave complication of brain ischemia and is the main cause of herniation and death. Although astrocytic swelling is the main contributor to cytotoxic edema, the molecular mechanism involved in this process remains elusive. N-myc downstream-regulated gene 2 (NDRG2), a well-studied tumor suppressor gene, is mainly expressed in astrocytes in mammalian brains. Here, we found that NDRG2 deficiency leads to worsened cerebral edema, imbalanced Na + transfer, and astrocyte swelling after ischemia. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 77 publications
0
9
0
Order By: Relevance
“…It has also been reported that relatively small changes in the brain water content can reflect large changes in the absolute water content of the brain and brain swelling ( Keep et al, 2012 ). Thus, cerebral edema caused by hyponatremia can result in massive cerebral swelling, subsequently increased intracranial pressure, rapid neurological deterioration, and increased morbidity and mortality following ischemic stroke ( Chen et al, 2021 ; Guo et al, 2021 ). Our study found that patients with hyponatremia had higher NIHSS scores at admission than those without hyponatremia.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that relatively small changes in the brain water content can reflect large changes in the absolute water content of the brain and brain swelling ( Keep et al, 2012 ). Thus, cerebral edema caused by hyponatremia can result in massive cerebral swelling, subsequently increased intracranial pressure, rapid neurological deterioration, and increased morbidity and mortality following ischemic stroke ( Chen et al, 2021 ; Guo et al, 2021 ). Our study found that patients with hyponatremia had higher NIHSS scores at admission than those without hyponatremia.…”
Section: Discussionmentioning
confidence: 99%
“…We previously rst found that Ndrg2-knockout male mice had much larger cerebral infarction volumes compared with wild-type male mice [11]. We further found that Ndrg2 knockouts male mice aggravates injury due to brain edema following cerebral ischemia [12]. These results demonstrate that Ndrg2 could be a potential target for the neuroprotection against cerebral ischemia in male mice.…”
Section: Introductionmentioning
confidence: 63%
“…Ma et al have found that MYC was involved in ischemia–hypoxia-induced astrocyte apoptosis 50 . Some studies have found that MYC downstream-regulated genes can protect the integrity of blood–brain barrier and cerebral edema following cerebral ischemia 51,52 . Ewida et al reported that HIF1A can improve the prognosis of stroke by activating angiogenesis 53,54 .…”
Section: Discussionmentioning
confidence: 99%